2015
DOI: 10.1016/j.aucc.2014.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The extent and application of patient diaries in Australian intensive care units: A national survey

Abstract: Patient diary use appears to be in its infancy in Australia with a lack of guiding policy for format and processes including evaluation. Nurses using diaries were enthusiastic about the initiative, holding optimistic perceptions about the potential positive impact of diaries on patient and family outcomes. Further research on their efficacy is required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 31 publications
0
13
0
4
Order By: Relevance
“…Nurses in Scandinavia have shown ambivalence toward legal issues in the diary concept, balancing the need for a therapeutic tool while adhering to patient protection laws. In Australia, ICU diaries have been received with similar mixed feelings as nurses try to integrate the need for guidelines and family‐centred care with issues of legal ambiguity (Nair et al ., ). In Austria, the legal question for consent has been resolved by asking the family to consent in principle if an ICU diary is written.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Nurses in Scandinavia have shown ambivalence toward legal issues in the diary concept, balancing the need for a therapeutic tool while adhering to patient protection laws. In Australia, ICU diaries have been received with similar mixed feelings as nurses try to integrate the need for guidelines and family‐centred care with issues of legal ambiguity (Nair et al ., ). In Austria, the legal question for consent has been resolved by asking the family to consent in principle if an ICU diary is written.…”
Section: Discussionmentioning
confidence: 97%
“…The next step was to conduct interviews with ICU nurses to describe the application of ICU diaries in Austria. This project is a replication of a study conducted in Demark (Egerod et al ., ), which has since been replicated in Sweden, Norway, Germany and Australia (Åkerman et al ., ; Gjengedal et al ., ; Nair et al ., ; Nydahl et al ., ). We want to demonstrate how diaries were introduced across Austria, rather than concentrating on a few regions as was performed in other countries.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…A review of nurse‐led follow‐up practices in Scandinavia has shown that diaries were written in about two‐thirds of the Swedish units and about half of the Danish ICUs (Egerod et al., ). Scandinavian nurses started writing ICU diaries in the early 1990s, and still this initiative seems to be more widespread in Scandinavia compared with other countries where diaries have been introduced more recently (Egerod, Storli, & Akerman, ; Heindl et al., ; Nair, Mitchell, & Keogh, ; Nydahl et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…recently (Egerod, Storli, & Akerman, 2011;Heindl et al, 2016;Nair, Mitchell, & Keogh, 2015;Nydahl et al, 2015).…”
Section: Discussionmentioning
confidence: 99%